2019
DOI: 10.22175/mmb2019.09.0040
|View full text |Cite
|
Sign up to set email alerts
|

Do Published Cooking Temperatures Correspond with Consumer and Chef Perceptions of Steak Degrees of Doneness?

Abstract: The objective of this study was to assess consumer and chef perceptions and knowledge of beef degrees of doneness (DOD) as well as to measure the changes in cooked color over time related to DOD. Steaks from strip loins (M. longissimus lumborum) from each of 5 quality treatments were used for this study. Steaks were cooked to an endpoint temperature of either very-rare (54°C), rare (60°C), medium-rare (63°C), medium (71°C), well-done (77°C), or very well-done (82°C). L*, a*, and b* were evaluated at 0, 1, 2, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
1
6
0
3
Order By: Relevance
“…Finally, for b *, the values increased over time within each degree of doneness, but the changes were more prevalent at lower (very rare, 54°C and rare, 60°C) degrees of doneness. The b * values increased at each successive time point within very rare samples, but were similar across the final three time points for well‐done steaks (Prill, Drey, Rice, et al., 2019).…”
Section: Effect Of Degree Of Doneness On the Sensory Properties Of Meatmentioning
confidence: 81%
See 4 more Smart Citations
“…Finally, for b *, the values increased over time within each degree of doneness, but the changes were more prevalent at lower (very rare, 54°C and rare, 60°C) degrees of doneness. The b * values increased at each successive time point within very rare samples, but were similar across the final three time points for well‐done steaks (Prill, Drey, Rice, et al., 2019).…”
Section: Effect Of Degree Of Doneness On the Sensory Properties Of Meatmentioning
confidence: 81%
“…In a similar study, the authors found time × degree of doneness interactions ( p < 0.05) for the Commission Internationale d’ Eclairage L *, a *, and b * (CIEL* a * b *) color values (Prill, Drey, Rice, et al., 2019). As the degree of doneness increased from very‐rare to well‐done, the internal color changed from lighter (high L * values) to darker (low L * values) over time.…”
Section: Effect Of Degree Of Doneness On the Sensory Properties Of Meatmentioning
confidence: 83%
See 3 more Smart Citations